Psychic Income Associated With Shanghai Tennis Masters and Residents’ Attitude - Zhang, Fengyun; Liu, Dongfeng; Plumley, Daniel; Chai, Mengyan (Frontiers in Psychology, 2022)
Using Shanghai Tennis Masters as an example, this study seeks to explore the psychic income associated with major sports events hosting and whether psychic income would predict local residents attitude toward events hosting. In addition, the moderating effect of sport involvement on the relationship between psychic income and attitude is also tested. Through structured questionnaires, data were collected from 1302 residents from Shanghai. A series of statistical analysis were conducted by using SPSS to examine the reliability and validity of the scales and to test the hypotheses. The results showed that the event has brought significant level of psychic income to the local community, and the perceived psychic income would predict residents’ attitude toward the event hosting. The moderating effect of sports involvement on the relationship between psychic income and attitude is also confirmed.